Tri Hita Karana dalam Teks Agastya Parwa - Ida Bagus Subrahmaniam Saitya (Sphatika: Jurnal Teologi, 2020)
Agastya Parwa is an Old Javanese manuscript in the form of prose and is of relatively old age (Century IX-XI M). The Agastya Parwa text is closely related to the name Ṛṣi Agastya as a Hindu Mahaṛṣi who contributed to the spread of Hinduism from the Sindhu river valley throughout India, Central Asia, China, Japan, and Indonesia. According to the literature, the Agastya Parwa text belongs to the parwa group, the Agastya Parwa text is also used as a source for yajña, this means this text belongs to the ceremonial group, but there are also those who declare this text included in the ethics group because the text This contains teachings about ethics, but the text of Agastya Parwa also contains the teachings of God. Tri Hita Karana which means three causes of happiness, consists of parhyangan, pawongan, and palemahan. Parhyangan in this text is taught that devotion to God must be based on a sincere, unconditional sincerity that can cause good for someone in this life and in the life to come. The form of pawongan in the Agastya Parwa text is self-control, this is very important for someone, people who are able to control themselves will get enlightenment. Palemahan explains that animals and plants are human siblings because animals and plants are descended from the ṛṣi.